ANOMIE DI TENGAH PERUBAHAN SOSIAL - Rusyi Syahra (LIPI Press, 2000)
It has become an awareness to many that in addition the visible economic and monetm y crisis on the surface, Indonesia is currently undergoing a multidimensional crisis that has resulted in social discontent and intergroup conflicts in various parts oft he country. It is widely held that the main cause of all the crises is the disruption of moral authority on the part of government officials and the military due to the widespread mismanagement of the past government. This article is devoted to explain the current multidimensional crisis and its destabilizing impact on the society fi'om the sociological concept of anomie. The concept, first introduced in the turn of the I 9th century by Emile Durkheim, a grand theorist of sociology, seeks to explain the nature of normlessless or anomie on the part of individuals and the whole society as the result of a tremendous and sudden social change. Further, a brief account is provided 011 how the concept has heen developed and used until recentlv by a number of social scientists in explaining the impacts of political turmoil and profound economic changes on national security and societal living condition of many countries oft he world. The article finally suggests a method that could be developed to detect and prevent social conflicts and unrests that may take place in the future.